Predictors for limb loss among patient with diabetic foot infections: an observational retrospective multicentric study in Turkey. (July 2015) - Saltoglu, N.; Yemisen, M.; Ergonul, O.; Kadanali, A.; Karagoz, G.; Batirel, A.; Ak, O.; Eraksoy, H.; Cagatay, A.; Vatan, A.; Sengoz, G.; Pehlivanoglu, F.; et al.
Abstract: We aimed to investigate the predictors for limb loss among patients with diabetes who have complicated skin/soft-tissue infections. In this observational study, consecutive patients with diabetic foot infection (DFI) from 17 centres in Turkey, between May 2011 and May 2013 were included. The Turkish DFI Working Group performed the study. Predictors of limb loss were investigated by multivariate analysis. In total, 455 patients with DFI were included. Median age was 61 years, 68% were male, 65% of the patients were hospitalized, 52% of the patients had used antibiotics within the last month, and 121 (27%) had osteomyelitis. Of the 208 microorganisms isolated, 92 (44.2%) were Gram-positive cocci and 114 (54.8%) were Gram-negative rods (GNR). The most common GNR was Pseudomonas ; the second was Escherichia coli, with extended spectrum β-lactamase positivity of 33%. Methicillin-resistant Staphylococcus species were found in 14% (29/208). Amputations were performed in 126/455 (28%) patients, 44/126 (34%) of these were major amputations. In multivariate analysis, significant predictors for limb loss were, male gender (OR 1.75, 95% CI 1.04–2.96, p 0.034), duration of diabetes >20 years (OR 1.9, 95% CI 1.18–3.11, p 0.008), infected ulcer versus cellulitis (OR 1.9, 95% CI 1.11–3.18, p 0.019), history of peripheral vascular disease (OR 2, 95% CI 1.26–3.27, p 0.004), retinopathy (OR 2.25, 95% CI 1.19–4.25, p 0.012), erythrocyte sedimentation rate >70 mm/hr (OR 1.6, 95% CI 1.01–2.68, p 0.05), and infection with GNR (OR 1.8, 95% CI 1.08–3.02, p 0.02). Multivariate analysis revealed that, besides the known risk factors such as male gender, duration of diabetes >20 years, infected ulcers, history of peripheral vascular disease and retinopathy, detection of GNR was a significant predictor of limb loss.